Monitoring Kontrol Greenhouse untuk Budidaya Tanaman Bunga Krisan dengan LabView - Sukandar Sawidin; Olga Engelin Melo; Tracy Marsela (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
One of the plants that is cultivated in Tomohon City is Chrysanthemum. Nowadays, the cultivation of chrysanthemum in a greenhouse is still using the conventional method where farmers are difficult to manage the process of watering and light, therefore, the efflorescence of chrysanthemum plants is disturbed. Based on that case, a control system is created using a microcontroller Arduino to adjust the temperature, humidity, light, and watering of plants in the greenhouse, and to monitor the system in a PC using Labview and TCP/IP. The results show that the system has been running according to the plan. Based on the temperature control set point, the valve will be "on" to distribute water and reducing temperature until valve will be “off” when the temperature set point is reached. Moisture control is tested when the heater is “on” and distributes steam in the greenhouse. If humidity is detected lower than the set point value, the heater will be “off”. Light control testing begins since the seed is planted up to 10 weeks by controlling the lights at the night and setting the RTC (Real time clock) for 4 hours (09.00 pm to 01:00 am).